Disturbed Cartilage and Joint Homeostasis Resulting From a Loss of Mitogen‐Inducible Gene 6 in a Mouse Model of Joint Dysfunction. Issue 10 (October 2014) - Pest, Michael A.; Russell, Bailey A.; Zhang, Yu‐Wen; Jeong, Jae‐Wook; Beier, Frank
<x xml:space="preserve">Abstract</x> Objective Mitogen‐inducible gene 6 (MIG‐6) regulates epidermal growth factor receptor (EGFR) signaling in synovial joint tissues. Whole‐body knockout of the Mig6 gene in mice has been shown to induce osteoarthritis and joint degeneration. To evaluate the role of chondrocytes in this process, Mig6 was conditionally deleted from Col2a1‐expressing cell types in the cartilage of mice. Methods Bone and cartilage in the synovial joints of cartilage‐specific Mig6‐deleted (knockout [KO]) mice and control littermates were compared. Histologic staining and immunohistochemical analyses were used to evaluate joint pathology as well as the expression of key extracellular matrix and regulatory proteins. Calcified tissue in synovial joints was assessed by micro–computed tomography (micro‐CT) and whole‐skeleton staining. Results Formation of long bones was found to be normal in KO animals. Cartilage thickness and proteoglycan staining of articular cartilage in the knee joints of 12‐week‐old KO mice were increased as compared to controls, with higher cellularity throughout the tissue. Radiopaque chondro‐osseous nodules appeared in the knees of KO animals by 12 weeks of age and progressed to calcified bone–like tissue by 36 weeks of age. Nodules were also observed in the spine of 36‐week‐old animals. Erosion of bone at ligament entheses was evident by 12 weeks of age, by both histologic and micro‐CT assessment. Conclusion MIG‐6 expression in chondrocytes is important for the maintenance of cartilage and joint homeostasis. Dysregulation of EGFR signaling in chondrocytes results in anabolic activity in cartilage, but erosion of ligament entheses and the formation of ectopic chondro‐osseous nodules severely disturb joint physiology.